HUBUNGAN ANTARA PERHATIAN ORANG TUA DAN CARA BELAJAR DENGAN HASIL BELAJAR EKONOMI SISWA KELAS X SEMESTER GANJIL PADA SMAN 1 LABUHAN RATU LAMPUNG TIMUR TAHUN PELAJARAN 2012/2013 - Merlyn Widalismana; I Komang Winatha; Nurdin Nurdin (FKIP Unila, 2013)
The result is a lesson learned in the teaching and learning activities conducted in schools for the achievement of learning objectives. Assessment by teachers is to know the extent to which students follow a study carried out in schools. In the process of student learning will be considered successful if the student has attended learning to improve knowledge, attitudes, behavior becomes better, and perbutan or ability to do something that is reflected in student learning outcomes. Student learning outcomes depend on how the process of learning and attention parents play an important role in the learning process. In addition, parents are watching and guiding in the form of efforts to learn and meet the needs of the school. Affection lead parents to personal development and independent child has admirable qualities. Learning outcomes are also highly correlated with learning for each individual student has a different learning styles vary. Thus the ways of effective learning so students can maximize their learning outcomes.This study aimed to determine whether there is parental concern and how to learn the results of class X students studying economics SMAN 1 Labuhan Ratu Lampung Timur school year 2012/2013. The research method used in this research is descriptive associative approach and ex post facto survey. The population in this study are all class X students of SMAN 1 Labuhan Ratu Lampung Timur totaled 174 students, and the sample in this research were 118 students who calculated using Cochran formula. Data were collected through questionnaires, processed by computer through SPSS version 16. Examiners hypotheses using partial correlation formula and double or multiple correlation models.Based on the analysis of the data obtained the following results.1. There is a positive and significant relationship between parental concern with the results of class X students studying economics SMAN 1 Labuhan Queen East Lampung school year 2012/2013 are shown. This is evidenced by t count t table is 6.054 1.98. The test results also show that the probability of error to reject Ho and accept H1 amounted to 9.7%, as shown by the results of the calculation of significant magnitude t 0.097. 2. There is a positive and significant relationship between learning with learning outcomes economy class X SMAN 1 Labuhan Queen East Lampung school year 2012/2013 are shown. This is evidenced by t count t table is 6.069 1.98. The test results also show that the probability of error to reject Ho and accept H1 is at 8.5%, as shown by the results of the calculation of significant magnitude t 0.085. 3. There is a positive and significant relationship between parental concern and how to learn the results of class X students studying economics SMAN 1 Labuhan Queen East Lampung school year 2012/2013 are shown. This is indicated by the F count F table is 38.729 3.08.Keywords: Attention Parents, How to Learn, and learning outcomes Economy